Comparison of theoretical and experimental investigation of protonation process of some thiones in acid media - Mirjana S. Jankulovska, Vesna Dimova, Ilinka Spirevska, Milena Jankulovska (INŽENJERSKO DRUŠTVO ZA KOROZIJU Beograd, Kneza Miloša 9/I, Tel/fax (011) 3860 - 867 i (011) 3230 - 028 E-mail:editor@idk.org.rs; www.idk.org.rs E-mail:caslav.lacnjevac@gmail.com, 2021)
PM3 semiempirical method was used for quantum chemical investigation in order to investigate the electronic properties and to determine the protonation centre in 1,2,4-triazoline-3-thione molecule. Confirmation of protonation center in acid media of investigated compounds was made using the values of atomic charges, as well as, proton affinity values. The results from semiempirical calculations indicated that the protonation center in the thione molecule was the sulphur atom. The behavior of thiones was investigated in mineral acid media using UV spectroscopy. The influence of the strength of the acid and its anion on the protonation process was discussed using three different mineral acids (perchloric, hydrochloric and phosphoric acid) for protonation. The protonation process in perchloric and hydrochloric acid took place in one step, while in phosphoric acid was not finished even when its concentration was to the highest degree. The dissociation constants of protonated forms (pKBH+) and the solvation parameter m* values were calculated in accordance with „excess acidity” function method (Cox and Yates) using the absorbance data from the experimental and reconstructed spectra (Characteristic Vector Analysis (CVA)). The determined pKBH+ values in hydrochloric acid had more negative value than those obtained in perchloric acid media. The pKBH+ values were in agreement with the literature data for this class of compounds.
Keywords: 1,2,4-triazoline-3-thiones, protonation, dissociation constants, proton affinity, UVspectrophotometry, PM3 semiempirical method